Rapid Screening of an Acid‐Catalyzed Triglyceride Transesterification in a Mesoscale Reactor. Issue 3 (24th January 2019) - Al-Saadi, Luma Shihab; Alegría, Alexandra; Eze, Valentine C.; Harvey, Adam P.
Abstract: A mesoscale oscillatory baffled reactor (meso‐OBR) served as a continuous screening platform to rapidly investigate the operating conditions for acid‐catalyzed production of fatty acid methyl ester (FAME) from triglyceride feedstock. The acid catalyst was 4‐dodecylbenzenesulfonic acid (DBSA) and the triglyceride feedstock was rapeseed oil (RSO). The parameter space was explored by means of a design of experiments (DoE) methodology. The variables screened were methanol‐to‐RSO molar ratio, catalyst‐to‐oil molar ratio, and residence time. Over 98 % conversion of RSO to FAME could be achieved under optimized conditions. Abstract : A rapid, low‐temperature, acid‐catalyzed biodiesel process was developed being applicable for biodiesel production from refined triglyceride sources and low‐grade triglyceride feedstock with high levels of free fatty acids and water. Transesterification of rapeseed oil in the presence of an organic acid catalyst was performed in a meso‐oscillatory baffled reactor under moderate reaction conditions.